Is there a political subject for feminisms and for women who fight? - Millán Moncayo, Margara (2025)
I propose to pursue the idea of the political subject, conceiving it as a plurality of subjects who, although diverse and positioned differently within the social order, construct a common goal, which is the basis of their “subjecthood”. I return to the concept of subjecthood of the Ecuadorian-Mexican philosopher Bolívar Echeverría (2001), who conceives it linked to politicality as a condition of the social subject who, however, to unfold as a “political subject”, must meet certain characteristics, both of consciousness and practice. That is, the subjecthood of the social subject is related to its praxis. I think that this praxis is shaped by struggle and, in that sense, struggles may be diverse but have a common goal, as Angela Davis reminds us. I will approach the question of the political subject not in the abstract, but by proposing a diagnosis of the present. I consider it essential to contextualize the time and space of the subject because it is from this that its diversity and its communality derive. After the diagnosis that situates us in the present, we will move on to explore a series of concepts that feminist critical thought has developed to address the diversity of its subjectivity. With this, I aim to redefine what we understand by feminism, free it from the constraints of gender, and position it as a cultural critique.